Strangulated hernia of Winslow’s hiatus - Puig, Roberto (Cirugía del Uruguay, 2021)
This is the first observation made in Uruguay of Winslow hiatus hermiation. The author includes a bibliograohical review of this disease. Followed by an an.alysis of its ethiological, anatomic and clinical characteristics. Its high mortality is accounted for delayed diagnosis. Simple radiology of the abdomen is of value in permitting an early diagnosis.